LAYANAN KONSELING KELOMPOK DALAM MENGURANGI SIKAP PEOPLE PLEASER DENGAN PENDEKATAN REBT TEKNIK ROLE PLAYING - Muti'ah, Aulia; Yuriska Pragusma; Laura Rahmanesa Rihendry; Ugi Sugian; Evi Fitriyanti (IKIP Siliwangi, 2025)
The people pleaser attitude is the tendency of individuals to always please others in order to gain acceptance, even if it means sacrificing personal interests. This attitude can negatively impact mental health, self-esteem, and decision-making. This research aims to determine the effectiveness of counseling services using the Rational Emotive Behavior Therapy (REBT) approach with role-playing techniques in reducing the people pleaser attitude.The REBT approach is used to help students recognize and change the irrational thoughts underlying people-pleasing behavior, while role-playing techniques are applied to train the courage to express opinions and set personal boundaries in social situations. The subjects of this research consist of students who have a high tendency to be people pleasers based on the results of the initial assessment. This research is action research in guidance counseling (PTBK) that uses several methods including Planning, Action, Information Gathering, and Reflection. This PTBK research collected data using pre-test and post-test questionnaires (cycle 1 and cycle 2), observations, interviews, and documentation studies. The analysis results showed that group counseling services with the REBT approach and role-playing techniques effectively reduced people-pleasing attitudes in eight students, marked by a change in mindset from irrational to rational, which had a positive impact on their emotional behavior.